LAYANAN BIMBINGAN KARIR DAN EFIKASI DIRI TERHADAP KEMATANGAN KARIR SISWA SMK - Vinne Khusnia Alfiatul Laila; Wiwik Sulistiani; Lutfi Arya (Fakultas Psikologi Universitas Hang Tuah, 2019)
This study aims to determine the significant influence between career counseling services and self efficacy on career maturity of students of the Indo Baruna cruise. This research uses a quantitative approach with survey research method, Using multiple regression analysis technique. Collecting data using questionnaire compiled using Likert scale, with details of career maturity scale of 48 items, 40 career advisory service scores, and self-efficacy scale of 36 items. The number of subjects in this study were 98 students from class X and class XI. The sampling technique in this research is with a saturated sampling technique. The results showed that the hypothesis that there was a significant influence between career guidance services and self efficacy at Indo Baruna cruise Surabaya accepted, with a 20.2% contribution. The first minor hypothesis was received by a contribution of 17.1%. The second minor hypothesis there was a significant influence between self efficacy on career maturity of studentsof Indo Indouna cruise received, with 8.8% contribution.